The Effect Of Traditional Saline Solution Concentration And Fermentation Duration On The Quality Of Tilapia Sauce - Putra, Leody Yuwono; Moch. Amin Alamsjah; Dwi Yuli Pujiastuti; Shofy Mubarak (Universitas Islam Lamongan, 2025)
The fermentation process has been known for a long time, this process basically occurs in a food. At the beginning of its appearance, the fermentation process is used by many western countries to create a food that has many flavors. In tilapia, there are carbohydrates, protein, fat, as well as a number of vitamins B3, B12, potassium, phosphorus, and selenium. For many people, besides being high in nutrition, and having a savory and sweet taste, fish sauce is also very easy to make and the cost to make it is quite cheap and doesn't take a long time. The aim of this study was to determine the effect of traditional salt concentration and the effect of fermentation time on the quality of fish sauce. The research method used was an experiment with Completely Randomized Design (CRD) as the experimental design. The treatments used were the addition of saline solution concentration and fermentation duration, each treatment was repeated 3 times. The independent variables in this study were the concentration of traditional salt used and the time of fermentation. The controlled variables in this study were Streptococcus lactis bacteria, pineapple fruit, temperature, pH and tilapia. The dependent variable measured was the quality of tilapia fish sauce using proximate analysis and NaCl test in percent (%). In this investigation, the optimal treatment was a 7-day fermentation with a 5% saline solution concentration (W3K1), with a protein content of 17.38%, water content of 68.66%, ash content of 8.12%, fat content of 10.85%, and 0% carbohydrate content